2016
DOI: 10.9734/bjast/2016/20021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Shell and Tube Heat Exchangers with Varying Tube Layouts

Abstract: Shell and tube heat exchangers (STHEs) are the most common type of heat exchangers and are applicable for wide range of operating temperatures and pressures. Numerical analyses on thermalhydraulic performance of three sets of shell and tube heat exchangers (STHEs) with different geometrical tube layout patterns variations namely; triangular (30º, STHE_T), rotated triangular (60º, STHE_RT) and the combined (STHE_C) patterns were carried out in this study. The results from solving the governing continuity, momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…The research found that pressure loss from helical baffles and vibrational stress might be reduced by using twin segmental baffles. Petinin and Dare [5] investigated triangular rotating shell-and-tube heat exchangers. The study found that triangular shell and tube heat exchangers are superior because they transmit more heat with the same amount of pressure loss.…”
Section: Literature Surveymentioning
confidence: 99%
“…The research found that pressure loss from helical baffles and vibrational stress might be reduced by using twin segmental baffles. Petinin and Dare [5] investigated triangular rotating shell-and-tube heat exchangers. The study found that triangular shell and tube heat exchangers are superior because they transmit more heat with the same amount of pressure loss.…”
Section: Literature Surveymentioning
confidence: 99%
“…Exchangers with Varying Tube Layouts Using CFD [15] In this study, heat exchanger is vertically cut-plane sections for velocity distributions of tube side fluid. Shell and tube heat exchangers increase in fluid velocity which result in decrease in fluid density because shell side is heated up.…”
Section: B Studying Performance Of Shell and Tube Heatmentioning
confidence: 99%
“…El principio básico de operación es muy simple ya que ambos fluidos a diferentes temperaturas son puestos en contacto cercano para efectuar el intercambio de calor, pero se previene su mezclado por medio de algún tipo de barrera metálica (haz de tubos). Se emplean deflectores o bafles en la coraza para dirigir el flujo del fluido y como soporte para los tubos, incrementando de esta manera la turbulencia del fluido y, con ello, la tasa de transferencia de calor [7]. Hasta la fecha varios autores han estudiado la operación y funcionamiento de condensadores.…”
Section: Index Terms-condenser Ethanol Percent Excess Area Thermalunclassified